0328 Social Jetlag Decreases Across the Lifespan: A Longitudinal Big Data Analysis of Objective Sleep. (25th May 2022) - Gottlieb, Elie; Gahan, Luke; Danoff-Burg, Sharon; Rus, Holly; Watson, Nathaniel; Raymann, Roy
Abstract: Introduction: Changes in social zeitgebers across the lifespan likely impact the interplay between biological and social clocks that fosters the circadian misalignment seen in social jetlag. Extant literature is limited to self-reported methods and cross-sectional designs and suggests older adulthood may be associated with a reduction in social jetlag given declining social obligations occurring after retirement. Using longitudinal ecologically-valid data, we examined the association between age as a continuous measure and social jetlag. We also examined whether work cessation is associated with a reduction in social jetlag. Methods: Data from 2, 446 users (mean age: 52.2 +/- 15.8, 51.8% female) across 473, 113 nights were included in the analysis from the PSG-validated SleepScore Mobile Application, which uses a non-contact sonar-based method to objectively capture sleep-related metrics and self-reported lifestyle. Social jetlag (expressed in minutes) was defined as the difference between midsleep times on week and weekend days from a user's total recording period. Linear regressions were used for the analysis. Age was examined as a both continuous variable, and as a dummy variable in a subsequent analyses in a subgroup of older adults, serving as a proxy for pre– (n = 604, age: 54-64, mean age: 60.5 +/- 2.8) and post-retirement (n = 428, age: 65-75, mean age: 69.9 +/- 2.8). Results: Linear regressions revealed a significant negative association between overall age and social jetlag, whereby older age was associated with a reduction in social jetlag (ß=-0.64, SE=0.082, p<0.0001). In agreement with this finding, post-retirement age was associated with a significant reduction in social jetlag (ß=-15.31, SE=3.78, p<0.0001) as compared to pre-retirement. Conclusion: The present analysis showed that social jetlag decreases across the lifespan, and its reduction appears to be amplified following retirement. Our findings are in-line with prior work demonstrating the reduction, but not extinction, of social jetlag in older adulthood. Support (If Any):